The stratigraphy and depositional environment of the late Precambrian Georgeville Group, Antigonish Highlands, Nova Scotia - Murphy, J.; Keppie, J. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1987)
The Antigonish Highlands are predominantly underlain by late Precambrlan rocks unconformably overlain by a limited area of Paleozoic rocks. The late Precambrlan rocks are here defined as the Georgeville Group which is subdivided into several formations. In the northern highlands (Georgeville block) the succession is as follows: (i) the Chisholra Brook Formation made up of interbedded mafic volcanic rocks, marble and mudstone; (li) the Morar Brook Formation composed of mudstone and siltstone with minor chert and limestone; and (ill) the Livingstone Cove Formation characterized by matrix-supported conglomerate interbedded with mudstone, chert and limestone. In the southern highlands (Keppoch block) the succession starts with the Keppoch Formation which is composed of calcalkaline-tholeiitic, subaerial to submarine bimodal volcanic rocks lnterlayered toward the top with mudstone. This unit is overlain conformably to unconformably by greywackes and mudstones of the James River Formation. In the central Antigonish Highlands (Maple Ridge and Clydesdale blocks), the rocks are mainly sedimentary with minor volcanic rocks. Here, the succession is: (1) the Maple Ridge Formation composed of interbedded mudstone, siltstone and thin greywacke: (ii) the James River Formation made up of conglomerate, greywacke siltstone and shale; (Hi) the Clydesdale Formation consisting mainly of alkalic basalts lnterlayered with minor greywacke and shale; and (iv) the South Rights Formation composed almost entirely of shales and slltstones. The stratigraphic sequence of the Georgeville Group suggests the progressive development of a sedimentary basin. The sedimentary rocks are interpreted as turbidites deposited in a periarc basin. Two gross llthological trends may be discerned: (i) vertically the sequence shows an upward coarsening and thickening (progradation) followed by an upward fining and thinning (regression), and (ii) laterally the grain size of the rocks decreases from north to south. These trends are interpreted in terms of a laterally migrating turbidite fan producing the observed prograda tion and regression with a volcanic arc source lying to the northwest. This sedimentological model is consistent with the nature of the volcanism which indicates an initial rift setting within a volcanic arc followed by oceanic island volcanism within the basin.